2019
DOI: 10.1002/jclp.22826
|View full text |Cite
|
Sign up to set email alerts
|

Convergence between Thematic Apperception Test (TAT) and self‐report: Another look at some old questions

Abstract: Objective This study extends upon the investigation of the influence of response format on the convergence between performance‐based and self‐report assessments of similar mental health constructs, to further examine the role of method variance in poor heteromethod convergence. Methods An online sample of 455 participants (57% male; mean age = 35.5 years) completed a multiple‐choice adaptation of the Thematic Apperception Test (TAT)—the Iowa Picture Interpretation Test (IPIT)—and two self‐report instruments: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The low intercorrelations between the pCRT-II subscales and the other measures may be partly traced back to the different nature of the assessment procedures. Specifically, several studies compared the results obtained with self-report and performance-based tests and found essential differences between them (Hartmann & Opaas, 2023; McCredie & Morey, 2019; Morey & McCredie, 2019). It is plausible to assume that the different methods assess the complex organization of a system (i.e., personality or relationship) at a unique level (Meyer, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The low intercorrelations between the pCRT-II subscales and the other measures may be partly traced back to the different nature of the assessment procedures. Specifically, several studies compared the results obtained with self-report and performance-based tests and found essential differences between them (Hartmann & Opaas, 2023; McCredie & Morey, 2019; Morey & McCredie, 2019). It is plausible to assume that the different methods assess the complex organization of a system (i.e., personality or relationship) at a unique level (Meyer, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Thematic Apperception Test is a test tool developed by Christina Morgan and Henry Murray, the theoretical basis of this test is that a human will give a view of his position in an ambiguous problem [12][13] [14]. Subconsciously the subject of the TAT will write a "character" analogy of a picture of the problem from his point of view.…”
Section: Thematic Apperception Test (Tat)mentioning
confidence: 99%